Women and Lung Cancer: Literature Assumptions and News from Recent Publications - Tiziana Vavalà; Silvia Novello (European Medical Journal Oncology, 2014)
For a long period of time, lung cancer (LC) was considered as a malignancy affecting only males, but epidemiological data have shown a dramatic increase of the incidence of this disease among women, and the gender gap has been narrowing steadily since the 1980s, mainly as a consequence of the huge spread of tobacco consumption during the past 70 years. In 2013, the percentage of current cigarette smokers among adults aged 18 and over in the US was 19.9% for men and 15.2% for women (selected estimates based on data from the January-June 2013 National Health Interview Survey), reflecting the earlier and more marked decline in the prevalence of tobacco use in men. Nowadays, cigarette smoking accounts for >90% of LCs in men and 75-85% of LCs in women in the US and Europe, but 20% of women with LCs have never smoked. Many studies describe differences between males and females in the clinical presentation and biology of LC, suggesting that the disease should be considered a specific entity in women, where adenocarcinoma is the most common histological subtype, and prognosis and response to treatment appear to be different. In line with these findings, hormonal receptors have been isolated in LC tissues: the interaction of oestrogen receptors with growth-factor-receptor signalling is an emerging area of investigation and – considering the potential impact of hormonal factors – lung carcinogenesis appears distinctive in women. Despite these considerations, no ‘gender driven’ diagnostic or therapeutic approaches are available nowadays. Improving knowledge of LC in women will allow identification of specific genetic alterations or hormonal profiles which could be targeted by therapy in order to stimulate research progress towards personalised sex-based investigations.